P529 Exposure–response relationship of vedolizumab subcutaneous treatment in patients with ulcerative colitis: VISIBLE 1. (25th January 2019) - Rosario, M; Polhamus, D; Dirks, N; Lock, R; Yao, X; Chen, J; Chen, C; Sun, W; Feagan, B; Sandborn, W; D'Haens, G
Abstract: Background: Vedolizumab is a gut-selective, humanised, monoclonal α4β7 integrin antibody approved for intravenous (IV) administration to treat adult patients with moderate–severe ulcerative colitis (UC). The VISIBLE 1 study assessed the efficacy and safety of a novel vedolizumab formulation for subcutaneous (SC) administration in adult patients with moderate–severe UC. We report the exposure–response and immunogenicity results for vedolizumab SC vs. vedolizumab IV. Pharmacokinetic (PK) and exposure–response data for vedolizumab IV are published. 1, 2 Methods: VISIBLE 1 (NCT02611830) was a Phase 3, double-blind, double-dummy, randomised, placebo-controlled trial. After open-label vedolizumab IV induction treatment (300 mg IV at Weeks [Weeks] 0 and 2), patients with a clinical response at WK6 were randomised to maintenance treatment with placebo, vedolizumab 108 mg every 2 weeks SC, or vedolizumab 300 mg every 8 weeks IV. PK serum samples were taken at prespecified time points. Descriptive statistics were used to summarise vedolizumab PK and immunogenicity using a drug-tolerant electrochemiluminescence assay. Vedolizumab trough concentrations (Ctrough ) at WK46 (the final comparable trough sample) were grouped by quartiles and clinical outcome rates were calculated. Results: A total of 216 patients were randomised to placebo ( n = 56), vedolizumab SC ( n = 106), and vedolizumab IV ( n = 54). Both higher vedolizumab SC Ctrough and vedolizumab IV Ctrough concentrations were associated with greater efficacy at WK52, with improved response for low-exposure patients in the SC arm. An increase in WK52 clinical remission was observed in both arms, from 50% to 83% of patients in SC and from 18% to 90% in IV. An increase in WK52 mucosal healing was observed in 50% to 89% of patients in SC and 27% to 100% of patients in IV. A similar trend was observed for both predicted steady-state average concentration and troughs. WK52 exposure–response results for vedolizumab IV were generally comparable with GEMINI 1 results. [1] Immunogenicity was similar for vedolizumab SC and IV and was not associated with injection-site or hypersensitivity reactions. Conclusions: Exposure–response relationships in VISIBLE 1 were similar to those seen previously in GEMINI 1. 1, 2 Higher serum concentrations of vedolizumab with SC and IV administration during maintenance therapy are associated with greater proportions of patients achieving clinical remission and mucosal healing. References 1. Rosario M, Dirks NL, Milch C, et al . A review of the clinical pharmacokinetics, pharmacodynamics, and immunogenicity of vedolizumab. Clin Pharmacokinet 2017;56:1287-1301. 2. Feagan BG, Rutgeerts P, Sands BE et al. Vedolizumab as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2013;369:699–710.